Non-specific and ski-specific performance development in peri-pubertal cross-country skiers - Zoppirolli, C.; Modena, R.; Bortolan, L.; Schena, F.; Pellegrini, B. (European Journal of Applied Physiology, 2023)
Purpose To evaluate non-specific and ski-specific performance development in male (M) and female (F) peri-pubertal cross-country skiers and to evaluate their relationship with cross-country skiing (XCS) performance and biological maturation within each age category and sex.